Modelling immune systems responses for the development of energy sharing strategies for swarm robotic systems - Al Haek, Mohammed; Ismail , Amelia Ritahani; Nordin, Azlin; Sulaiman, Suriani; Hui, Keng Lau (2014)
This paper presents an initial investigation on studying an immune systems response; the granuloma formation for the inspirations on the development of energy sharing strategies for swarm robotic systems. Granuloma formation is a process in which unwanted substances are removed by immune systems. To better understand the components and the processes in granuloma formation, we modeled them using Unified Modelling Language (UML). Based on this model, analogous properties of the granuloma formation and swarm robotic systems are mapped accordingly. Based on these work energy sharing strategies which are inspired by the process in granuloma formation are proposed, in particular, for fault tolerance in swarm robotic systems.